2022
DOI: 10.1177/17474930221081639
|View full text |Cite
|
Sign up to set email alerts
|

Lenticulostriate artery length and middle cerebral artery plaque as predictors of early neurological deterioration in single subcortical infarction

Abstract: Background: Early neurological deterioration (END) is not a rare phenomenon in single subcortical infarction (SSI; traditionally known as lacunar infarction) patients. Predictors of END in SSI patients are uncertain. Aims: We aimed to investigate the association between infarct lesion characteristics, penetrating artery morphology, carrier artery plaque features and END using whole-brain vessel-wall imaging. Methods: We prospectively collected data from SSI patients without stenosis of the corresponding carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…32 However, previous studies including our own have suggested that it was the underlying pathogenesis rather than the size of the lesion that determined the END or prognosis in patients with SSI. 33,34 It is possible to interpret our data as supporting a link between perfusion change and CSVD-related LI, which would support Fisher's 'lacunar hypothesis'. 1,2 However, this hypothesis remains controversial, 35,36 with several studies suggesting that perfusion alteration does not play a significant role in the development of CSVD-related LI.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…32 However, previous studies including our own have suggested that it was the underlying pathogenesis rather than the size of the lesion that determined the END or prognosis in patients with SSI. 33,34 It is possible to interpret our data as supporting a link between perfusion change and CSVD-related LI, which would support Fisher's 'lacunar hypothesis'. 1,2 However, this hypothesis remains controversial, 35,36 with several studies suggesting that perfusion alteration does not play a significant role in the development of CSVD-related LI.…”
Section: Discussionsupporting
confidence: 77%
“… 32 However, previous studies including our own have suggested that it was the underlying pathogenesis rather than the size of the lesion that determined the END or prognosis in patients with SSI. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a slight change in IGV value may have a greater significance in distal SSI with a smaller lesion volume than in proximal SSI. Furthermore, proximal SSI occurs when the perforating artery/arteriole is occluded at the orifice level 1 , 20 , 29 . As mentioned earlier, considering that collateral flow is not developed well in these blood vessels, the occlusion of the orifice eventually causes blood supply failure to the distal area.…”
Section: Discussionmentioning
confidence: 99%
“…However, the etiology and pathogenesis of END in AIS patients are not fully understood. Studies have con rmed that impaired lateral circulation, thrombotic enlargement, cerebral edema, and hemorrhagic transformation are associated with END [6][7][8] , and that immune in ammation plays an important role in these pathophysiology.…”
Section: Introductionmentioning
confidence: 99%